The New Model Based on Secondary Electron Emission of Solid Materials on Its Electrostatic Electrification. Issue 3 (1st July 2015) - Chang, Tianhai; Wu, Shuling
Abstract : As the study to innovate and develop anew research direction of electrostatic theory, it is knownthat secondary electron emission coefficient of solid materialcan't be ignored as an important and incentive parameterof static electricity. In this paper, we combinedthe experiment with theoretical way to discuss and analyzethe association mechanism between the magnitudeand polarity of surface electrostatic potential with the secondaryelectron emission characteristic, as well as tried toexplore and establish the new model based on secondaryelectron emission characteristics with solid surface electrostaticcharging.